TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERSEROAN BERBASIS PEMBERDAYAAN MASYARAKAT KECAMATAN BULIK: - Mahdaniah; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2023)
Companies operating in the natural resources sector such as PT. Gemareksa Mekarsari in Lamandau Regency, Central Kalimantan Province, is obliged to carry out corporate social and environmental responsibilities. Formulation of the problem of how to fulfill the company's social and environmental responsibilities based on community empowerment in Bulik District, Central Kalimantan at PT. Gemareksa Mekarsari and what are the obstacles in its implementation. The research method used is normative law, descriptive in nature with juridical research methods, secondary data and qualitative analysis. Research results and discussion of analysis of TJSL implementation based on community empowerment at PT. Gemareksa Mekarsari has not run as it should, because it has not achieved what was expected in terms of community empowerment. There are obstacles such as lack of funds, lack of community involvement, and poor communication between the community and the Company which are still challenges in this regard. TJSL Conclusion The company has environmental problems and conditions that have not yet become the company's attention, and is in the midst of a community that is not happy with its existence. This dissatisfaction creates a negative image for the company, so that TJSL community empowerment is not running effectively.